2013
DOI: 10.1097/olq.0b013e318283d2c9
|View full text |Cite
|
Sign up to set email alerts
|

It Takes 2

Abstract: Objectives To identify partner attributes associated with sexually transmitted infections (STIs) among adolescents and summarize implications for research and prevention. Design Systematic review. Methods We identified peer-reviewed studies published 1990–2010 which assessed ≥1 partner attribute in relation to a biologically-confirmed STI among adolescents (15–24 years) by searching MEDLINE and included articles. Studies which included adolescents but >50% of the sample or with mean or median age ≥25 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 69 publications
(215 reference statements)
2
12
0
Order By: Relevance
“…The CDC has long cited recent new partners as a key C trachomatis risk that should prompt more frequent screening, (2) and is supported by more recent prospective studies. (9, 10) Our finding of risk from partners who have other partners is consistent with cross-sectional studies of partners' concurrency being linked to more STIs,(14, 15) and with the concept of sexual networks, in which a woman's risk is influenced by her relationship position and STI rates in the greater network. (16) Similarly, frequent substance use as a risk may reflect the woman's involvement in a higher-risk sexual network or riskier partner and condom practices.…”
Section: Discussionsupporting
confidence: 86%
“…The CDC has long cited recent new partners as a key C trachomatis risk that should prompt more frequent screening, (2) and is supported by more recent prospective studies. (9, 10) Our finding of risk from partners who have other partners is consistent with cross-sectional studies of partners' concurrency being linked to more STIs,(14, 15) and with the concept of sexual networks, in which a woman's risk is influenced by her relationship position and STI rates in the greater network. (16) Similarly, frequent substance use as a risk may reflect the woman's involvement in a higher-risk sexual network or riskier partner and condom practices.…”
Section: Discussionsupporting
confidence: 86%
“…Further combined with evidence that partner risk is associated with STD acquisition, 5,6,9 our findings suggest partner risk may contribute to the well-established link between alcohol use and STDs. 1 Therefore, adolescent in-the-moment alcohol use may synergistically increases risk by enhancing the probability of choosing a partner with an STD and decreasing the probability of using a condom with that partner.…”
Section: Discussionsupporting
confidence: 65%
“…Second, while we analyzed four partner characteristics, we were unable to consider additional important partner characteristics because either they were not measured (e.g., time since last STD, concurrent partners, relationship length) or because participant and partner drinking were too strongly correlated to consider partner drinking as an independent predictor. 6,9 The consistency, however, between partners drinking status is commonly reported. 7,12 Third, because only 12% of participants reported in-the-moment alcohol use, we were limited to assessing alcohol use as a dichotomous variable and were unable to examine differential effects by amounts of alcohol consumed.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding is consistent with a recent systematic review which concluded that older partner age was associated with prevalent infection but largely unrelated to incident STIs among adolescents. 29 …”
Section: Discussionmentioning
confidence: 99%